Body measurements of Merlangius merlangus during Alkor cruise AL608 - Luisa Listmann (PANGAEA, 2025)
This data set includes single fish whiting data collected during the RV ALKOR cruise AL608 conducted in March 2024 in the Western Baltic Sea by the University of Hamburg. The cruise was part of the 5-year MARSYS teaching cruise program of the University of Hamburg GFP20-1_047. All single fish measurements were made directly on board. Full wet weights of whitings were measured and sexes recorded.